Effect of cyclosporine on adriamycin induced nephritis - Japaulo, E. G.; Soares, V (Marcel Dekker Inc, 2002)
The effects of cyclosporine A (CSA) administration, started as early as renal lesion is induced, on the development of Adriamycin-induced nephropathy were assessed by comparing the time course of this nephropathy in rats receiving CSA with that in non-treated animals (group ADR) over 16 weeks. Throughout the experiment, no significant difference in proteinuria was observed between the groups. At the end of the experiment, there was no significant difference between the groups regarding the frequency of glomerular lesion (Group AADR: Md=23%, P25=15%, P75=75%; Group ADR-CSA: Md=48%, P25=11%, P75=70%); tubulointerstitial lesion index (Group ADR: Md=1.5, P25=1.0, P75=2.5); glomerulosclerosis area (Group ADR = 18.2 +/- 4.2%; Group ADR-CSA = 13.2 +/- 1.4%); and, interstitial fibrosis area (Group ADR+V: 1.75 +/- 0.10%; group ADR-CSA: 1.34 +/- 0.09%). In conclusion, CSA, when, administered since nephropathy induction does not change the course of the disease.
Keywords: adriamycin nephropathy; cyclosporine A; CSA; proteinuria; tubulointerstitial fibrosis; glomerulosclerosis